2021
DOI: 10.3390/app11062808
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Recycling Return of Integrated Circuits Using Computer Vision on Printed Circuit Boards

Abstract: The technological growth of the last decades has brought many improvements in daily life, but also concerns on how to deal with electronic waste. Electrical and electronic equipment waste is the fastest-growing rate in the industrialized world. One of the elements of electronic equipment is the printed circuit board (PCB) and almost every electronic equipment has a PCB inside it. While waste PCB (WPCB) recycling may result in the recovery of potentially precious materials and the reuse of some components, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…YOLOv3 stands out over YOLOv2 primarily due to its Feature Pyramid Network (FPN) architecture, facilitating multi-scale prediction and effective small object detection [12]. Silva et al [13] employed a pretrained YOLOv3 model, fine-tuned using the PCB DSLR dataset [14], to detect ICs in waste PCBs, facilitating their recycling process. Addressing the concern of missing components in PCB assembly, Khare et al [15] proposed a solution involving object detection, image subtraction, and pixel manipulation to mitigate the issue of absent components within PCBs.…”
Section: ) One-stage Detector: Yolomentioning
confidence: 99%
See 1 more Smart Citation
“…YOLOv3 stands out over YOLOv2 primarily due to its Feature Pyramid Network (FPN) architecture, facilitating multi-scale prediction and effective small object detection [12]. Silva et al [13] employed a pretrained YOLOv3 model, fine-tuned using the PCB DSLR dataset [14], to detect ICs in waste PCBs, facilitating their recycling process. Addressing the concern of missing components in PCB assembly, Khare et al [15] proposed a solution involving object detection, image subtraction, and pixel manipulation to mitigate the issue of absent components within PCBs.…”
Section: ) One-stage Detector: Yolomentioning
confidence: 99%
“…In this study, YOLOv4, by default, uses a set of nine anchor sizes for 416 input size: 10,13, 16,30, 33,23, 30,61, 62,45, 59,119, 116,90, 156,198, 373,326, which encompasses various scales and aspect ratios and is also termed the anchor size set of YOLOv3. Additionally, the study explores another set of anchor sizes (13,31,21,42,31,15,34,58,51,29,57,98,78,48,150,118,255,323) derived from [2]. This alternative anchor size set is tailored explicitly from a dataset of PCB electronic components.…”
Section: ) Efficientnet-yolov4mentioning
confidence: 99%
“…Gd, Ho, and Sm showed small to insignificant differences ranging between 0.40 and 2.10% as a function of the acids used. Due to the nature of the sample, the low concentration of Au may be explained as (a) its main use in electrical-electronic equipment focuses on the internal structure of the integrated circuits and the protection of electrical contacts from environmental conditions such as oxidation; and (b) MLCCs in gold-plated terminals are used in specific and high-cost applications, so their potential presence in the sample is minimal, with external LED drivers and LME being the most likely origin [12,19,73]. Increased concentrations of Ag and Pd may be explained as multi-layer ceramic capacitors being one of the main electrotechnical applications of Ag and, simultaneously, the main electrotechnical application of Pd.…”
Section: Characterisation Of Mlccs From Lighting Equipment Via Icp-oe...mentioning
confidence: 99%
“…In particular, the presence of significant quantities of precious metals with a high economic value supports the effort to recover them from urban mines and the viability of recycling plants. It is worth noting that, for the year 2019, the stored mass of specific precious metals in e-waste corresponded to Ag 1200 t, Au 200 t, Ir 1 t, Ru 0.3 t, and Pd 100 t [2,[11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies [5,6], hazardous cadmium, arsenic, chromium, and antimony were also identified in PCBs. The total composition of printed circuit boards has been analyzed by many researchers [7][8][9][10][11][12]. PCBs usually contain 40% metals, 30% plastics, and 30% ceramic materials, although their actual composition varies depending on the intended use of the device.…”
Section: Introductionmentioning
confidence: 99%